An estimate of syphilis incidence in Eastern Europe - Liam J. Herbert; Stephen I. Middleton (Edinburgh University Global Health Society, 2012)
Eastern Europe experienced epidemic levels of syphilis after the collapse of the Soviet Union. Presently data are less comprehensive outside the European Union (EU) and European Free Trade Association (EFTA). This review aims to identify published papers with suitable data to estimate a regional burden of disease for syphilis in the 19 member countries of Eastern Europe.